The use of image analysis techniques for the study of muscle melanisation in sand flathead (Platycephalus bassensis). (1st January 2022) - Ooi, Chun Kit; Lewis, Trevor; Nowak, Barbara; Lyle, Jeremy; Haddy, James
Abstract: Muscle melanisation in sand flathead is visible as black spots in the normally white flesh of fish. It is widespread in Tasmania, including at the Tamar Estuary, with increasing frequency of reporting by recreational fishers. The phenomenon is more prevalent in areas impacted by heavy metal pollution and has been linked to heavy metal accumulation. In this study, image processing software ImageJ was employed to study the phenomenon and to establish an objective rating system. A longitudinal profile plot was used to study the greying of the fillet. The degree of melanisation was rated based on the percentage surface area melanised on the surface and in transverse sections of fillets. A muscle melanisation scoring system for sand flathead was established based on visual interpretation using the macroscopic melanisation scoring criteria: melanisation scores 0 = <0.5%, 1 = 0.5–5%, 2 = 5–20%, and 3 = >20% (% = melanised surface area in proportion to the whole fillet). A refined image analysis technique was developed to quantify the percentage of melanised muscle surface area and the muscle melanisation scoring system was statistically validated. Sand flathead fillet with higher melanisation score was shown to be linked to increased intensity of greyness and greater numbers and size of black spots on the surface of fillets and within the flesh. The greying and black spots were primarily concentrated at the anterior region of fillet and around the dorsal vertebrae zone on transverse section of fillets. Overall, findings from this study established the use of image analysis techniques to validate visual inspection and to give a standardised and objective method to determine the degree of melanisation in sand flathead. As muscle melanisation appears to be linked to heavy metal pollution, the standardised scoring system would facilitate future research for environmental pollution and monitoring purposes. Graphical abstract: Image 1 Highlights: Muscle melanisation scoring system was standardised and statistically validated. Black spots and greying were significantly greater at higher melanisation score. Greying was significantly greater in the anterior region of fillet. Distribution of black spots was concentrated around the dorsal vertebrae area.